Prevalence and Seroprevalence of Covid-19 in Suspected Malaria During the Second Wave in Yaounde, Cameroon - Esther Voundi-Voundi; Isabelle-Claire Mene Tenku; Junior Voundi-Voundi; Marie Paule Ngogang; Nadège Lylian Doumou A Mvomo; Christiane Medi-Sike; Michel Toukam (HEALTH SCIENCES AND DISEASE, 2023)
Background. The COVID-19 pandemic has added an additional burden in countries with already fragile health systems. Our objective was to determine the prevalence and seroprevalence of COVID-19 in suspected malaria during the second wave in Yaounde. Methods. A descriptive cross-sectional study was conducted at the Jordan Medical Services for 8 weeks from April 19 to June 13, 2021, i.e., during the second wave in Cameroon. For the 86 patients with suspected malaria, nasopharyngeal and blood samples were taken for SARS-CoV-2 antigen and anti-SARS-CoV-2 IgG and IgM using the STANDARD TM Q COVID-19 Ag kit from SD BIOSENSOR, Korea, 2020 and Standard TM Q COVID 19 Ac IgG/IgM kit from SD BIOSENSOR, Korea, 2020 respectively. Confirmation of malaria was done by microscopic examination of stained blood smears. Results. Malaria was confirmed in 20.9% (18) of cases. The prevalences of COVID-19 and COVID-19/malaria co-infection were 8.1% and 0.9% respectively. Of the 25.6% (54) of patients with anti-COVID-19 IgM, no positive microscopic cases were found. On the other hand, a little more than half of the patients had IgG antibodies against COVID-19 whether they had a positive thick drop or not (56.0% (42/75) and 52.2% (71/136) respectively). Conclusion. In case of suspicion of malaria in a malaria area, it seems important to consider COVID-19 as a differential diagnosis.